Comparison of transmission abilities of four Cicadulina species vectors of maize streak virus from Nigeria - Oluwafemi, S.; Jackai, L.E.N.; Alegbejo, M.D. (Wiley, 2007)
Four Cicadulina species [Cicadulina arachidis China, Cicadulina dabrowskii Webb, Cicadulina mbila (Naude), and Cicadulina storeyi China (Homoptera: Cicadellidae)] found during field surveys in 1997–1999 across five ecological zones in Nigeria were reared in screenhouses and females were used in a study to compare their abilities to transmit Maize streak virus (Geminiviridae: genus Mastrevirus) from maize to maize using the susceptible variety Pool 16. The results showed that for both acquisition access feeding periods (AAP) and inoculation access feeding periods (IAP), transmission efficiencies decreased in the following order: C. storeyi > C. mbila > C. arachidis > C. dabrowskii. The transmission efficiencies of these vectors increased with longer feeding periods, as the means of susceptible test plants that showed Mastrevirus symptoms for both acquisition and IAPs were higher for 24 and 48 h than for 1 and 2 h for all four species studied. The epidemiological implications of these differences in transmission abilities are discussed.